Benefits of both physical assessment and electronic health record review to assess frailty prior to heart transplant. Issue 3 (6th January 2022) - Lee, Yoon Kyung; Shukman, Marina; Biniwale, Reshma; Ardehali, Abbas; Kamath, Megan; Nsair, Ali; Schaenman, Joanna M.; Goldwater, Deena
Abstract: Introduction: Frailty status affects outcomes after heart transplantation, but the optimal way to assess frailty prior to transplant remains unknown. Methods: This single‐center,  observational study assessed 44 heart transplant candidates for frailty using three methods. The Short Physical Performance Battery (SPPB) and Fried Frailty Phenotype (FFP) were used as two physical assessments of frailty. The Frailty Risk Score (FRS) was used as a chart‐review based assessment measuring 20 different biopsychosocial and functional components, including biomarkers, depression, cognitive impairment, and sleep. Results: We determined the correlation between FRS, SPPB, and FFP and how each correlated with clinical outcomes. Of 44 participants, mean age was 60 years. FRS correlated with SPPB and FFP ( P  = .043, P  < .001, respectively). Higher frailty as measured by SPPB and FRS was significantly associated with lack of achieving waitlist status ( P  = .022; P  = .002) and not being transplanted ( P  = .026; P  = .008). Higher frailty by SPPB and FFP was also associated with mortality ( P  = .010; P  = .025). Conclusion: SPPB and chart‐review FRS showed potential for predicting waitlist and transplant status of heart transplant candidates, while SPPB and FFP were associated with mortality. Additional studies may serve to validate these observations.